Transverse seismic response and failure mode of towers of a cable-stayed bridge full-model: Tests and simulations. (April 2021) - Xie, Wen; Sun, Limin
Highlights: Seismic damage and failure mode of a bridge full-model were studied experimentally. The tower appeared in an unexpected failure mode with double plastic hinges. The tower firstly suffered from severe damage under earthquake excitations. A numerical model was verified via the test results of the bridge full-model. Abstract: Severe damage to towers of cable-stayed bridges have been recorded in past actual earthquakes. Therefore, increasing attention has been devoted to the seismic failure of cable-stayed bridges under strong earthquakes. However, few experimental studies focus on the seismic failure of long-span cable-stayed bridges including both superstructures and substructures under strong earthquakes. In this paper, a 1/70-scaled bridge full-model was designed and assembled following a 1400 m-span cable-stayed bridge, which was composed of the towers, girder, cables, piers, pile groups, and artificial soil placed in four shear boxes. Shaking table tests were conducted to study the seismic response and potential failure mode of towers of the bridge full-model under transverse earthquake excitation. Test results show that the tower exhibits an unexpected failure mode with the double plastic hinges, which reveals a new feature for the seismic failure of the tower of super long-span cable-stayed bridges. The plastic hinges are firstly observed at near the junction region between the tower and lower beam, then at the proximal joint portion between the tower and upper beam. The tower firstly suffers from severe damage or even local failure for the bridge full-model under strong earthquakes, but it could carry the vertical load. The seismic damage evaluated by the curvature criteria or residual displacements are in good agreement with the observed damage under earthquake excitation with low shaking amplitudes. Moreover, numerical modeling of the bridge full-model could effectively predict the dynamic properties and seismic response of the bridge full-model, and capture the character of the failure mode of the towers compared to the test results.